MODERN APPROACHES TO ACCOUNTING AND TAXATION IN ENVIRONMENTAL ENTREPRENEURSHIP - Т. Murovana (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Actual issues of accounting and taxation at enterprises of green business under the terms of realization of state environmental policy of Ukraine are investigated. Ways of improving methodology of accounting in accordance with International Financial Reporting Standards, legal regulation of calculation taxes and charges and control over its payment to the budget are defined and proved for the purpose of simplifying business activities and increasing investment prospects of green businesses enterprises in Ukraine.